Publisher Correction: Endothelial progeria induces adipose tissue senescence and impairs insulin sensitivity through senescence associated secretory phenotype - Agian Jeffilano Barinda; Koji Ikeda; Dhite Bayu Nugroho; Donytra Arby Wardhana; Naoto Sasaki; Sakiko Honda; Ryota Urata; Satoaki Matoba; Ken-ichi Hirata; Noriaki Emoto (Nature Communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.